Judaisms : a twenty-first-century introduction to Jews and Jewish identities - Hahn Tapper, Aaron J. (Aaron Joshua) (University of California Press, 2016)
"An introductory textbook that examines how Jews are a culture, ethnicity, nation, nationality, race, and religion. With each chapter revolving around a single theme--Narratives, Sinais, Zions, Messiahs, Laws, Mysticisms, Cultures, Movements, Genocides, Powers, Borders, and Futures--this introductory textbook interrogates readers' understanding of the Jewish community. Written for a new mode of teaching--one that recognizes the core role that identity formation plays in our lives--this book weaves together alternative, marginalized voices to illustrate how Jews have always been in the process of reshaping their customs, practices, and beliefs. Judaisms is the first book to assess and summarize Jewish history from the time of the Hebrew Bible through today using multiple perspectives"--Provided by publisher